Experimental results from dielectric-metal grating coupled surface plasmon resonance device for novel low-cost biosensor Miguel - Ponce Camacho, Miguel Ángel (My University, 2018)
An optical prototype was fabricated to perform measurements of surface plasmon polaritons in light beams diffracted at angles of less than 900. Experiments were developed to identify the excitation resonant angle of surface polariton plasmons by a diffraction grating with a pitch greater than the wavelength of the light signal. In the laboratory tests, measurements of the intensity curve of the diffracted light signal were carried out in the +1 and -1 orders. The experimental results were consistent with the theoretical approach. Based on this method, it is proposed a device for a low cost biosensor, using nanomaterial that can be functionalized with bio-material.
Keywords: Optical prototype; Nanomaterial; Biomaterial; Campus Mexicali